Manajemen Kepala Sekolah dalam Meningkatkan Kinerja Guru di Sekolah Dasar Negeri 19 Kuta Makmur - Junawi (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to (1) Analyze the principal's planning in improving teacher performance; (2) Analyze the principal's strategy in improving teacher performance; (3) Analyzing evaluations carried out by school principals in improving teacher performance. The research method used is qualitative research with a descriptive approach. This research was carried out at Kuta Makmur 19 Public Elementary School, North Aceh. The results of this research are the principal's planning and strategies for improving teacher performance at SDN 19 Kuta Makmur elementary school as well as evaluating teacher performance. The planning stage is carried out at the beginning of school meetings which are scheduled at the beginning of the semester and the end of the year. Meanwhile, the principal's strategy for improving teacher performance is to involve all teachers in the principal's work programs such as training, seminars and teacher group work. After this, the principal will carry out evaluation actions on these teachers in order to follow up on the results of the principal's previous planning